Exogenously Supplied Compatible Solutes Rapidly Ameliorate NaCl-induced Potassium Efflux from Barley Roots - Cuin, Tracey Ann; Shabala, Sergey (Plant and cell physiology, 2005)
It has been suggested that the role of compatible solutes in plant stress responses is not limited to conventional osmotic adjustment, but also includes some other regulatory or osmoprotective functions. In this study, we hypothesized that one such function is in maintaining cytosolic K⁺ homeostasis by preventing NaCl-induced K⁺ leakage from the cell, a feature that may confer salt tolerance in many species, particularly in barley. This hypothesis was investigated using the non-invasive microelectrode ion flux (MIFE) measuring technique. We show that low (0.5-5 mM) concentrations of exogenously supplied proline or betaine significantly reduced NaCl-induced K⁺ efflux from barley roots in a dose-response manner. This effect was instantaneous, implying that large intracellular concentrations of compatible solutes are not required for an amelioratory role. Exogenously supplied betaine also significantly enhanced NaCl-induced H⁺ efflux, but only in pre-incubated roots, implying some alternative mechanism of regulation. Sap K⁺ and Na⁺ analysis and membrane potential measurements are also consistent with the model that one function of compatible solutes is in maintaining cytosolic K⁺ homeostasis by preventing NaCl-induced K⁺ leakage from the cell, possibly through the enhanced activity of H⁺-ATPase, controlling voltage-dependent outward-rectifying K⁺ channels and creating the electrochemical gradient necessary for secondary ion transport processes. These data provide the first direct evidence for regulation of ion fluxes across the plasma membrane by physiologically relevant low concentrations of compatible solutes.